Managing Neuropathic Pain in the Diabetic Patient - Boulton, Andrew J M.; Vileikyte, Loretta; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd., 2009)
Managing Neuropathic Pain in the Diabetic Patient (second edition) provides a concise, didactic and essential resource for clinicians in the management of neuropathic pain. The opening overviews of epidemiology, classification and clinical features are augmented in this edition by a discussion of the negative effect of painful neuropathic symptoms on quality of life. These are followed by a chapter on diagnosis and staging, which includes approaches to history taking, clinical examination, pain assessment scales, testing and staging. The book concludes with a chapter on both pharmacological and non-pharmacological approaches to management of neuropathic pain. The concise handbook format makes Managing Neuropathic Pain in the Diabetic Patient an invaluable reference for primary care practitioners and diabetologists who wish to keep up to date in the diagnosis and management of neuropathic pain.
to diabetic neuropathies -- Classification and clinical features -- Diagnosis and staging -- Management of neuropathic pain.
Keywords: Popular works; Science; Medicine; Education; Popular Science; Popular Science in Education; Medicine/Public Health, general; Science, general; Electronic books